Бифуркации Андронова – Хопфа в волновых моделях торсионных колебаний бурильных колонн - Гуляев, В.И.; Гайдайчук, В.В.; Глушакова, О.В. (Прикладная механика, 2010)
A wave model of torsional vibrations of rotating drill strings is constructed. The ranges of values of the corresponding to self-vibrations regimes angular velocities are found. In the limiting these ranges states the Andronov – Hopf bifurcations are realizing. The main regularities of appearance and passing the self-vibration processes are established.